2020
DOI: 10.1101/2020.11.16.20232009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The total number and mass of SARS-CoV-2 virions

Abstract: Quantitatively describing the time course of the SARS-CoV-2 infection within an infected individual is important for understanding the current global pandemic and possible ways to combat it. Here we integrate the best current knowledge about the abundance of potential SARS-CoV-2 host cells and typical concentrations of virions in bodily fluids to estimate the total number and mass of SARS-CoV-2 virions in an infected person. We estimate that each infected person carries 109-1011 virions during peak infection, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 79 publications
3
68
0
2
Order By: Relevance
“…The cytopathic effect was observed from approx. 10 4 RNA copies/mL, which, with the infectious particles:RNA ratio in the tissues ranging typically between 1:1000 and 1:10,000 [ 10 , 11 ] corresponds to 1–10 infectious particles/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The cytopathic effect was observed from approx. 10 4 RNA copies/mL, which, with the infectious particles:RNA ratio in the tissues ranging typically between 1:1000 and 1:10,000 [ 10 , 11 ] corresponds to 1–10 infectious particles/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The method sensitivity was verified through a serial dilution of the virus stock suspension (3 × 10 11 RNA copies/ml), both without and after freezing at −80 °C. The cytopathic effect was observed from ∼10 4 RNA copies/ml, which corresponds to 1–10 infectious particles/ml [ 14 , 15 ]. To verify that samples after freezing were not compromised, we performed (besides the above-described verification of the method sensitivity) also an analysis before and after freezing on 10 real-world samples with cycle thresholds 25–30 (5 samples) and 30–40 (5 samples).…”
Section: Methodsmentioning
confidence: 99%
“…The 46-kDa SARS-CoV-2 Nucleocapsid (N) protein is 89.1% identical to SARS-CoV N. Genomic analysis of human coronaviruses indicated that N might be the major factor conferring the enhanced pathogenicity to SARS-CoV-2 [4]. N represents the most abundant viral protein in the infected cell [12][13][14], with each assembled virion containing approximately one thousand molecules of N [15]. Given that each infected cell can contain up to 10 5 virions (infectious, defective and incomplete overall) [14], the number of N molecules in an infected cell can reach 10 8 , accounting for ~1% of a total number of cellular proteins (~10 10 [16]).…”
Section: Introductionmentioning
confidence: 99%